The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5888/pcd13.160005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Financial Stress and Positive Financial Behaviors on Cost-Related Nonadherence to Health Regimens Among Adults in a Community-Based Setting

Abstract: IntroductionLittle is known about the role of positive financial behaviors (behaviors that allow maintenance of financial stability with financial resources) in mitigating cost-related nonadherence (CRN) to health regimens. This study examined the relationships between positive financial behaviors, financial stress, and CRN.MethodsData came from the 2011 Speak to Your Health! Community Survey (n = 1,234). Descriptive statistics were computed to examine financial stress and CRN, by chronic condition and health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
(30 reference statements)
1
22
1
1
Order By: Relevance
“…For example, there is evidence that perceived sense of control acts as a buffer against the effect of socioeconomic disadvantage (42). Several studies have reported success in increasing adherence by using positive affect/self-affirmation (43), mindfulness-based stress reduction (44), and financial literacy interventions to reduce financial stress (45).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is evidence that perceived sense of control acts as a buffer against the effect of socioeconomic disadvantage (42). Several studies have reported success in increasing adherence by using positive affect/self-affirmation (43), mindfulness-based stress reduction (44), and financial literacy interventions to reduce financial stress (45).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a private health system, financial objective stress may mean a patient cannot afford to purchase treatment or continue to adhere to treatment. In a mixed health system, the potential effect of subjective strain may be greater as this is linked to psychological distress 26 and a greater likelihood of cost-related nonadherence to health regimes, 27 rather than forgoing or not attending treatment due to cost. A holistic appreciation of survivor financial hardship therefore becomes pertinent in a mixed public health care system.…”
Section: Relevance Of Objective Stress and Subjective Strain In A Mmentioning
confidence: 99%
“…States which chose not to expand Medicaid had lower cancer screening rates, particularly amongst federally qualified health centers, while those expanding Medicaid had an increase in early stage cancer diagnosis in the working-age population[ 22 ], suggesting that reducing financial barriers to care by expanding public health insurance coverage increases utilization of services that have been shown to improve healthcare outcomes[ 23 ]. Additional socioeconomic factors that may interfere with utilization of preventative measures in this population include lack of transportation[ 24 , 25 ], work hours conflicting with medical office hours[ 26 ], and reduced health literacy[ 27 ]. Additionally, patient knowledge of their medical problems has been shown to correlate with improved adherence to HCC surveillance ultrasound[ 24 ], creating another barrier to adherence for a population at risk for reduced health literacy.…”
Section: Discussionmentioning
confidence: 99%